2004
DOI: 10.1016/j.devcel.2004.10.016
|View full text |Cite
|
Sign up to set email alerts
|

EGF Receptor Signaling Regulates Pulses of Cell Delamination from the Drosophila Ectoderm

Abstract: Many different intercellular signaling pathways are known but, for most, it is unclear whether they can generate oscillating cell behaviors. Here we use time-lapse analysis of Drosophila embryogenesis to show that oenocytes delaminate from the ectoderm in discrete bursts of three. This pulsatile process has a 1 hour period, occurs without cell division, and requires a localized EGF receptor (EGFR) response. High-threshold EGFR targets are sequentially activated in rings of three cells, prefiguring the temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
(3 reference statements)
1
25
0
Order By: Relevance
“…Since the pattern of rho transcription was not sharply focused in the tracheal placode, it is likely that the secreted Spitz ligand is broadly distributed. The circular spread of EGFR activation from this crude distribution of EGFR ligand might require feedback regulation of EGFR signaling (Shilo, 2005), as has been shown in other cases (Brodu et al, 2004;Wasserman and Freeman, 1998).…”
Section: Research Articlementioning
confidence: 71%
“…Since the pattern of rho transcription was not sharply focused in the tracheal placode, it is likely that the secreted Spitz ligand is broadly distributed. The circular spread of EGFR activation from this crude distribution of EGFR ligand might require feedback regulation of EGFR signaling (Shilo, 2005), as has been shown in other cases (Brodu et al, 2004;Wasserman and Freeman, 1998).…”
Section: Research Articlementioning
confidence: 71%
“…In particular, a subset of abdominal SOPs activates rho to promote EGF secretion, and the amount of rho expressed positively correlates with the number of oenocytes that develop (Brodu et al, 2004). We previously identified a rho CRM (RhoBAD) that is sufficient to recapitulate abdominal SOP expression and found that an Abd-A/Hth/Exd complex restricts the binding of the Sens repressor to RhoBAD (Li-Kroeger et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, rho expression in abdominal SOPs leads to EGF secretion and the induction of oenocytes (Elstob et al, 2001;Rusten et al, 2001). Importantly, the number of oenocytes produced in each segment is dependent upon the level of EGF signaling, making oenocyte enumeration a functional readout of rho expression (Brodu et al, 2004). For example, the ectopic expression of Abd-A in thoracic segments activates rho expression to induce oenocytes, whereas the genetic removal of abd-A abolishes rho expression in abdominal SOPs and results in the complete loss of oenocytes ( Fig.…”
Section: Research Articlementioning
confidence: 99%
“…In the DA3 lineage, it seems that Dpp, Wg and Ras signaling act on one col cis element and the Hox proteins on others. The regulation of col expression by Hox proteins in different tissues via different CRMs provides a new paradigm to decipher how different Hox paralogs cooperate and/or collaborate with tissue-and lineage-specific factors to specify cellular identity (Brodu et al, 2004;Gebelein et al, 2004;Walsh and Carroll, 2007;Stobe et al, 2009).…”
Section: Modular Cis Regulation Of Col Transcription By Hox Proteinsmentioning
confidence: 99%